Pioglitazone Effect on Clinical Outcome and Inflammatory Response in patients with type 2 diabetes mellitus and COVID-19: A Randomized Clinical Trial - Eman Elmekaty (14777932) (2024)
Background The pandemic of COVID-19 infection has emerged as a rapidly spreading communicable disease across the globe. Patients with diabetes mellitus are at a higher risk of mortality from COVID-19, mainly due to the chronic. inflammatory state associated with diabetes. It was hypothesized that Pioglitazone - a medicine used to treat diabetes with proven anti-inflammatory properties – may improve COVID-19 outcomes in patients with diabetes. The aim of this study was to evaluate the efficacy of pioglitazone in improving the clinical outcomes of patients with type 2 diabetes (T2D) admitted with moderate-severe COVID-19. Methods Eligible patients with T2D and admitted with COVID-19 to the hospitals in Qatar and Kuwait were randomized in a double-blind fashion to receive either pioglitazone 45mg orally daily for 10 days then 30mg daily for 18 days or a matching placebo. The study had 2 primary outcomes: (1) the incidence of a clinical composite outcome of a) requirement for mechanical ventilation, b) death, c) myocardial damage indicated by Troponin > 3x upper limit of normal range; and 2) an increase in C-reactive protein (CRP). Blood samples were collected at baseline and repeated weekly until day 28 or discharge. Results Total of 343 patients, pioglitazone (n=188) and placebo (n=155), were enrolled in the study. Twenty-eight participants met the primary clinical composite outcome. There was no significant difference in the incidence of primary outcome between subjects receiving placebo (n=14) and pioglitazone (n=14). Cox Hazard ratio for patients receiving pioglitazone was 1.10 (p=NS). A total of 4 patients died in the placebo group vs. 3 in the pioglitazone group (p =0.91). No statistically significant difference was observed between the two groups in plasma CRP level at the end of the follow-up. Conclusion Pioglitazone treatment did not provide any additional clinical benefit to patients with T2D admitted with COVID-19 infection.